Recombinant thrombomodulin may protect cardiac capillary endothelial glycocalyx through promoting Glypican-1 expression under experimental endotoxemia. Issue 11 (November 2022) - Kakino, Yoshinori; Doi, Tomoaki; Okada, Hideshi; Suzuki, Kodai; Takada, Chihiro; Tomita, Hiroyuki; Asano, Hirotaka; Kano, Soichiro; Wakayama, Yugo; Okuda, Tomoki; Fukuda, Hirotsugu; Nishio, Ayane; et al.
Abstract: Introduction: Myocardial dysfunction occurs in patients with sepsis due to vascular endothelial injury. Recombinant human thrombomodulin (rhTM) attenuates vascular endothelial injuries through endothelial glycocalyx (eGC) protection. Hypothesis: We hypothesized that rhTM attenuates myocardial dysfunction via the inhibition of vascular endothelial injury during sepsis. Methods: Ten-week-old male C57BL6 mice were injected intraperitoneally with 20 mg/kg of lipopolysaccharide (LPS). In rhTM-treated mice, rhTM was injected intraperitoneally at 3 and 24 h after LPS injection. Saline was injected intraperitoneally as control. To assess for eGC injury, intensity score was measured 48 h after the LPS injection. To confirm vascular endothelial injuries, ultrastructural analysis was performed using scanning (SEM) and transmission electron microscopy (TEM). Results: The survival rate of the rhTM group at 48 h after LPS injection was significantly higher than that of the control group (68% vs. 17%, p < 0.05). The serum level of troponin I in the rhTM group was lower than that in the control (2.2 ± 0.4 ng/dL vs 9.4 ± 1.1 ng/dL, p < 0.05). The expression of interleukin-6 (IL-6) was attenuated in the rhTM-treated group than in the control (65.3 ± 15.3 ng/mL vs 226.3 ± 19.4 ng/mL, p < 0.05). The serum concentration of syndecan-1, a marker of glycocalyx damage, was significantly decreased 48 h post-administration of LPS in the rhTM-treated group than in the control group. In ultrastructural analysis using SEM and TEM, eGC peeled off from the surface of the capillary lumen in the control. Conversely, the eGC injury was attenuated in the rhTM group. Gene set enrichment analysis revealed that osteomodulin, osteoglycin proline/arginine-rich end leucine-rich repeat protein, and glypican-1, which are proteoglycans, were preserved by rhTM treatment. Their protein expression was retained in endothelial cells. Conclusion: rhTM attenuates sepsis-induced myocardial dysfunction via eGC protection. Abstract : Vascular endothelium; Glycocalyx; Microvascular dysfunction; Thrombomodulin; Glypican-1.